How Does Popularity Information Affect Choices? A Field Experiment - Tucker, Catherine; Zhang, Juanjuan (Management science, 2011)
Popularity information is usually thought to reinforce existing sales trends by encouraging customers to flock to mainstream products with broad appeal. We suggest a countervailing market force: popularity information may benefit niche products with narrow appeal disproportionately, because the same level of popularity implies higher quality for narrow-appeal products than for broad-appeal products. We examine this hypothesis empirically using field experiment data from a website that lists wedding service vendors. Our findings are consistent with this hypothesis: narrow-appeal vendors receive more visits than equally popular broad-appeal vendors after the introduction of popularity information. This paper was accepted by Pradeep Chintagunta, marketing.